Estimating Discharge of Nitrogen in Zero Water Exchange at I-Sharp Setiu, Terengganu, Malaysia, Based on System Dynamic Approach - Muhamad Safiih Lola and Anton Abdulbasah Kamil (Nature Environment and Pollution Technology, 2021)
The present study was designed to display the integrated model of nitrogen discharge process (i.e. nitrites and nitrates; ammonia; chlorophyll and dissolved nitrogen, dissolved oxygen) which is part of the complete model of shrimp aquaculture of an Integrated Shrimp Aquaculture Park (i-Sharp) ecosystem in System Dynamic Model Aquaculture-System Policy (SD-AQEP). This study offers a comprehensive elaboration concerning the long-term process of nitrogen accumulation, as well as its effects on shrimp activities. Furthermore, the analysis of the model and the simulation results also show the conditions of nitrogen with several strategies for control and manipulation. For example, in situations where mixing of stock density is high and providing feed into ponds supplies is excessive, the nitrogen dynamic rapidly hits alarming levels. Aforementioned, the typical strategy in this setting such as stocking density and the best time to harvest could be established. Additionally, the model structure represents the discharge derived from the nitrogen process on varied settings of variables in aquaculture development. In conclusion, this model provides an experimental simulation platform that can be implemented by policy makers on long-term strategic management for developing or maintaining large-scale aquaculture development projects in the future.